The problem of identity in the global world - Вандишев, В М; Переломова, О С (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2017)
The article deals with identity in philosophical and ethical dimensions, and features of modern vision of the nature of identity in social and national dimensions. The concept of identity also considered in connection with the peculiarities of its representation in the Ukrainian community. The authors believe that there is a close connection between the fixed in public life sense of identity and responsibility of government. The attention is also paid to the importance of the meaning of phenomena of multiculturalism and identity in the modern world system, as well as to the use of social identity in hybrid ideology.